Graph-based Representation for Sentence Similarity Measure : A Comparative Analysis - Sakira Kamaruddin, Siti; Yusof, Yuhanis; Azzah Abu Bakar, Nur; Ahmed Tayie, Mohamed; Abdulsattar A.Jabbar Alkubaisi, Ghaith (International Journal of Engineering and Technology, 2018)
Textual data are a rich source of knowledge; hence, sentence comparison has become one of the important tasks in text mining related works. Most previous work in text comparison are performed at document level, research suggest that comparing sentence level text is a non-trivial problem.  One of the reason is two sentences can convey the same meaning with totally dissimilar words.  This paper presents the results of a comparative analysis on three representation schemes i.e. term frequency inverse document frequency, Latent Semantic Analysis and Graph based representation using three similarity measures i.e. Cosine, Dice coefficient and Jaccard similarity to compare the similarity of sentences.  Results reveal that the graph based representation and the Jaccard similarity measure outperforms the others in terms of precision, recall and F-measures.